An Examination of Strategic Anticipation of Appellate Court Preferences by Federal District Court Judges - Christina L. Boyd; James F. Spriggs II (Washington University Journal of Law & Policy, 2009)
This Essay tackles the complicated relationships within the federal judicial hierarchy with a focus on the relatively understudied connection between the Supreme Court and district courts.
Keywords: Judicial process; Federal courts; Federal judicial hierarchies; Federal judges; U.S. Supreme Court